Long-Term Consequences of Hepatitis C Viral Clearance on the CD4 (+) T Cell Lymphocyte Course in HIV/HCV Coinfected Patients - J. Dazley; R. Sison; J. Slim (AIDS Research and Treatment)
The long-term impact of pegylated-interferon plus ribavirin treatment outcome on CD4 T cell course in patients coinfected with human immunodeficiency virus and hepatitis C virus is largely unclear in the literature. The aim of this study was to investigate the impact of HCV-RNA clearance by standard anti-HCV therapy on long-term CD4 cells recovery in HIV/HCV patients on successful combined antiretroviral therapy. We retrospectively enrolled HIV/HCV-coinfected patients on HIV medications and treated for hepatitis C. CD4 + T cell counts were registered at baseline and after hepatitis C therapy. Multiple linear regression analysis was performed to identify independent predictors of CD4 + T cell change following the anti-HCV treatment outcome. Of the 116 patients enrolled, 54 (46.6%) reached a sustained virological response. During a follow-up of 24 months, the SVR group showed a mean annual increase in CD4 + T cell from baseline of 84 cells/ll at 1 year and of a further 38 cells/ll within the second year (P=0.01, 0.001, resp.). An insignificant mean increase of 77 cells/ll occurred in the non-SVR group within month 24 (P=0.06). Variables associated with greater CD4 gains were higher nadir, lower preinterferon CD4 counts, and lower body mass index (BMI).